Why We Harm - Presser, Lois (Book collections on Project MUSE., 2013)
Criminologists are primarily concerned with the analysis of actions that violate existing laws. But a growing number have begun analyzing crimes as actions that inflict harm, regardless of the applicability of legal sanctions. Even as they question standard definitions of crime as law-breaking, scholars of crime have few theoretical frameworks with which to understand the etiology of harmful action. In this book, the author scrutinizes accounts of acts as diverse as genocide, environmental degradation, war, torture, terrorism, homicide, rape, and meat-eating in order to develop an original theoretical framework with which to consider harmful actions and their causes. In doing so, this book presents a general theory of harm, revealing the commonalities between actions that impose suffering and cause destruction.